The Role of Ethnicity, Sexual Attitudes, and Sexual Behavior in Sexual Revictimization During the Transition to Emerging Adulthood - Rinehart, Jenny K. (Child Maltreat, 2014)
An experience of child sexual abuse (CSA) substantially increases women’s risk of adult sexual assault (ASA), but the mechanisms underlying this relationship are unclear. Previous research often has not examined the full range of ASA experiences or included the influence of ethnicity, sexual behavior, and sexual attitudes on CSA and severity of ASA. The current study utilized path analysis to explore the relationships among ethnicity, sexual attitudes, number of lifetime sexual partners, CSA, and severity of ASA in emerging adult women. Results indicated a significant relationship between CSA and more severe ASA that was partially explained by having more lifetime sexual partners. Additionally, European American women, relative to Hispanic women, reported more severe victimization, which was fully explained by more positive attitudes toward casual sex and having more lifetime sexual partners. These results have implications in the design and implementation of universal and selective prevention programs aimed at reducing ASA and revictimization among emerging adult women.